A mechanism study for trace phoxim in water extracted by DLLME with composite extractant containing ionic liquids. Issue 3 (23rd February 2020) - Fang, Jing; Liu, Ke; Li, Tingting; Zheng, Wenwen; Li, Chunli
Abstract: Dispersive liquid-liquid microextraction (DLLME) is a technology for enrichment extraction and detection of organic pesticide in samples. In this paper, 1-hexyl-3-methylimidazolium hexafluorophosphate ([HMIM][PF6 ]) and hexyl acetate (C8 H16 O2 ) were combined as a composite extractant. And it was used to extract and detect trace phoxim in water. Several important parameters had been investigated, such as volume ratio of [HMIM][PF6 ] and C8 H16 O2, ultrasonic time, ice bath and centrifugal time. The composite extractant was also applied to extracting trace amounts of phoxim in real water samples. Under the optimized experiment conditions, the spiked recoveries of phoxim in real water samples were 103.7% to 120.3%, and the relative standard deviations were 2.6% to 4.6%. The mechanism of DLLME was analyzed by quantum chemistry caculation. Analysis of electrostatic potential energy indicated that the addition of C8 H16 O2 reduced the electrostatic interaction between [HMIM] + and [PF6 ] − . Interaction energy analysis in composite extraction system indicated that composite extractant was more attractive to phoxim and more repulsive to water. So the selectivity of composite extractant to phoxim was enhanced compared with [HMIM][PF6 ]. Atoms in Molecules analysis indicated that the hydrogen bonds between [HMIM] + and [PF6 ] − were weaker in composite extractant. It leaded to the viscosity decrease . In the composite extractant system, number of hydrogen bonds formed between extractant and phoxim was more than that of [HMIM][PF6 ], and the interaction force was stronger. So the composite extractant had better extraction effect on phoxim. [HMIM][PF6 ] played a major extraction role in the composite extractant, and C8 H16 O2 played a synergistic extraction role. Graphical Abstract: